The TRAPD approach as a method for questionnaire translation - Walde, Peggy; Völlm, Birgit Angela (Frontiers in Psychiatry, 2023)
Surveys and questionnaires are widely used in various areas of psychological and psychiatric research and practice. Many instruments have been used in several languages and across cultural contexts. A popular method of choice for their translation into another language involves translation and back-translation. Unfortunately, this method’s ability to detect flaws in translation and necessities for cultural adaptation is limited. To address these shortcomings, the Translation, Review, Adjudication, Pretest, and Documentation (TRAPD) approach of questionnaire translation from cross-cultural survey design has been developed. In this approach, several translators with different professional backgrounds translate the questionnaire on their own first and then come together to discuss their versions. Since the translators’ expertise is required to vary (e.g., survey methodology experts, translation experts, expert knowledge in the questionnaire’s topic) the team approach results in a high-quality translation as well as offering opportunities for cultural adaptation. This article illustrates the application of the TRAPD approach on the basis of the translation process of the Forensic Restrictiveness Questionnaire from English into German. Differences and advantages are discussed.